Legal Status of Pharmacists in Indonesia: A Normative Analysis of Pharmaceutical Regulation: Kedudukan Apoteker dalam Sistem Kesehatan Indonesia: Analisis Normatif Regulasi Kefarmasian - Viviana Idris (Jurnal Riseta Soshum, 2026)
Pharmacists are an important element of health service systems, and there is a significant role in ensuring safe, effective, and rational use of drugs. This system of pharmacy practice continues to develop (as does the national health system) in Indonesia through a framework of laws and regulations. The purpose of this research is to analyze the legal status of pharmacist as a healthcare professional in accordance with Indonesian legislation and the ratio legiss of pharmaceutical laws. This research used a normative juridical approach with literature studies based on legal documents, government regulations and other scientific publication related to the pharmacy practice. The analysis based on government regulations shows that pharmacists as health practitioners have a strong legal legitimacy by 5 (five) regulations in the context of professional practice only, licensing, pharmaceutical services and patient safety. With regard to pharmaceutical product management and clinical pharmacy services, these regulations highlight that they fall under the umbrella of pharmaceutical practice. The national health system has also seen recent regulatory reforms that further enhance legal protection of pharmaceutical professionals while providing an avenue for higher quality healthcare services. The evolution of pharmaceutical regulation is also paradigm for the movement in pharmacy practice from a product-oriented to a patient-centred model of pharmaceutical care. Thus, recognizing the regulatory framework and the legal reasoning underpinning these policies is important to enhance pharmacists' professionalism as well as to promote safe and effective healthcare systems in Indonesia.